2005
DOI: 10.1136/adc.2005.078006
|View full text |Cite
|
Sign up to set email alerts
|

Hyperchloraemic metabolic acidosis following open cardiac surgery

Abstract: Aims: To describe acid-base derangements in children following open cardiac surgery on cardiopulmonary bypass (CPB), using the Fencl-Stewart strong ion approach. Methods: Prospective observational study set in the paediatric intensive care unit (PICU) of a university children's hospital. Arterial blood gas parameters, serum electrolytes, strong ion difference, strong ion gap (SIG), and partitioned base excess (BE) were measured and calculated on admission to PICU. Results: A total of 97 children, median age 57… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 40 publications
(40 reference statements)
0
21
0
2
Order By: Relevance
“…A TOT is mainly composed of albumin as the principal extracellular weak acid [17]. During CPB, patients develop a dilutional hypoalbuminaemia as a result of intravascular fluid administration [10,11,18]. This hypoalbuminaemia induces a metabolic alkalosis, which counteracts the acidosis induced by the administration of intravascular fluids [7,10].…”
Section: Discussionmentioning
confidence: 99%
“…A TOT is mainly composed of albumin as the principal extracellular weak acid [17]. During CPB, patients develop a dilutional hypoalbuminaemia as a result of intravascular fluid administration [10,11,18]. This hypoalbuminaemia induces a metabolic alkalosis, which counteracts the acidosis induced by the administration of intravascular fluids [7,10].…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the modern ion selective method, 20,21,26 the following reference values for strong electrolytes and weak acids were adopted: Na 140 mmol l À1 , K 4 mmol l À1 , Cl 108 mmol l À1 , Ca 2.3 mmol l À1 , Mg 0.8 mmol l À1 , lactate 1.5 mmol l À1 , albumin 42 g l À1 and phosphate 1.2 mmol l À1 . Therefore, according to Eqs.1 to 6, the value of SIG at reference state equals to 2.85 meq l À1 and the deviation of the observed SIG from its reference value can be expressed as:…”
Section: Theoretical Considerations and Mathematical Acidbase Calculamentioning
confidence: 99%
“…11 Importantly, several authors have suggested a significant relationship between the concentration of unmeasured anions as assessed by SIG and mortality in critically ill patients. [16][17][18][19][20][21] These efforts capitalized on extensive theoretical work, which has disclosed the quantitative interlinking between the base excess and the SID theory. In order to provide the clinician with easy-to-use tools for the assessment of acid-base equilibrium and, in particular the unmeasured ions, several authors have attempted to unify the SID and the base excess approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lactic acidosis might also develop during the operative and postoperative course depending on different parameters like CPB and cross-clamp duration and postoperative hemodynamic status [1, 5, 6]. Nonetheless, acid-base imbalances are present not only during the operation but also commonly in the postoperative phase, which are then of all sorts, with acidosis prevailing [1, 7, 8]. Severe manifestation causes, among others, impairments of the cardiovascular system with concomitant systemic consequences [9–11].…”
Section: Introductionmentioning
confidence: 99%